2011
DOI: 10.1007/978-3-642-23768-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Improving Computer Security Dialogs

Abstract: Abstract. Security dialogs warn users about security threats on their computers; however, people often ignore these important communications. This paper explores the links between warning dialog design and user understanding of, motivation to respond to, and actual response to computer security warnings. We measured these variables through a 733-participant online study that tested a set of four existing computer security warnings and two redesigned versions of each across low-and high-risk conditions. In some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…All three textual elements are based on past studies which used the same or similar textual content in various contexts [9,17,22,30]. For instance, Maimon, Alper, Sobesto and Cukier [22] used similar content to inform hackers about risks they incur if they penetrate organizational systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three textual elements are based on past studies which used the same or similar textual content in various contexts [9,17,22,30]. For instance, Maimon, Alper, Sobesto and Cukier [22] used similar content to inform hackers about risks they incur if they penetrate organizational systems.…”
Section: Methodsmentioning
confidence: 99%
“…Past research has tried to better understand how users interact with warnings and why users ignore them [9][10][11][12][13]. Mostly the focus was on examining the SSL web browser warning messages and their effectiveness [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Yee argues that "interrupting users with prompts presents security decisions in a terrible context: it teaches users that security issues obstruct their main task and trains them to dismiss prompts quickly and carelessly" (Yee 2004, p. 49). Bravo-Lillo et al (2011) suggest that interruptive security warnings are often ignored or suboptimally addressed because users have a limited cognitive ability to switch between tasks. Patil et al (2015) found that interruptive privacy notices on mobile devices are poorly attended to.…”
Section: Literature Review and Theorymentioning
confidence: 99%
“…Bravo-Lillo et al [6] showed empirically that warnings are not understoodfor example, due to technical terminology. Improved warning content may help, though: Biddle et al [5] found that their reformulated warnings made users more responsive to different levels of connection security.…”
Section: Prior Research On the Content Of Web Browser Warningsmentioning
confidence: 99%
“…on certificate warnings: Sunshine et al [19]) have shown that current warnings are ineffective at influencing the behavior of users for two main reasons: First, because of habituation effects from the frequent unhelpful warnings in non-critical situations [2]. Second, because of the technical language that prevents users from understanding the risks of proceeding -that is, how likely it is that an adverse event occurs and what the personal consequences are [6,8,13]. We thus not only need to prevent the occurrence of warnings in uncritical situations, but also make the warnings understandable so that the infrequent warnings will enable users to take informed decisions about proceeding based on the actual risks involved.…”
Section: Introductionmentioning
confidence: 99%